Research and Analysis on Virtual Classroom Teaching Models and Their Effectiveness—A Case Study of Basic Spanish Language Instruction in Chinese Universities - Luan, Yun; Luan, Yue (Journal of Educational Research and Policies, 2025)
With the increasing prevalence of virtual classrooms in education, scholars have conducted a series of comparative studies on traditional face-to-face instruction and virtual classroom teaching. Due to factors such as internet connectivity and teaching platforms, virtual classroom instruction encompasses various models. Currently, there is relatively limited research on the specific teaching formats within virtual classrooms. Given the distinct characteristics of foreign language learning—which requires learners to engage in interaction and practice rather than mere theoretical study—it is crucial for language educators to understand and select the most suitable virtual classroom teaching model based on instructional content and objectives. Furthermore, to achieve optimal teaching outcomes, instructors must thoroughly assess students’ feedback and evaluations of different teaching modules (e.g., reading, vocabulary, or grammar) to enhance instructional effectiveness. Therefore, this study focuses on first-year Spanish majors in Chinese universities to investigate virtual classroom teaching models. Specifically, it compares learners’ perceptions of pre-recorded and live-streamed classes across four modules—vocabulary, grammar, reading, and exercises—to explore their preferences for different instructional formats. The findings aim to assist teachers in tailoring classroom organization to the unique demands of each module.